Multi-head Watson–Crick automata. Issue 2 (2nd April 2016) - Chatterjee, Kingshuk; Ray, Kumar Sankar
ABSTRACT: Inspired by multi-head finite automata and Watson–Crick automata, in this paper, we introduce a new structure, namely multi-head Watson–Crick automata, where we replace the single tape of a multi-head finite automaton by a DNA double strand. The content of the second tape is determined using a complementarity relation similar to the Watson–Crick complementarity relation. We establish the superiority of our model over multi-head finite automata and also show that both the deterministic and non-deterministic variants of the model can accept non-regular unary languages. We also compare our model with parallel communicating Watson–Crick automata systems and prove that both of them have the same computational power.